AL-GHAZALI’S INFLUENCE ON MALAY TAFASIR: SPECIAL FOCUS ON REVELATION AND REASON - Nadzrah Ahmad (Journal of Islamic, Social, Economics and Development, 2023)
Discussions about reason and revelation are the most important parts of Islamic theology, namely the problem of knowing God and the problem of knowing good and evil. Discussion about this issue turned out to be a long debate among scholars from the classical period to contemporary times. Among the classical scholars whose thoughts are still used as references today is al-Ghazali, who has been regarded as the reviver or the Islamic reformer (al-mujaddid) of the 5th century AH of Islam and has been credited with various titles, of which the most famous is Hujjat al-Islam (Proof of Islam). Al-Ghazali’s writings and teachings have had a significant impact on Muslim intellectual traditions, including in the Malay Archipelago, which shaped the interpretation of the Qur’an in Malay tafasir. Remarkably the revelation and reason aspect has been incorporated into the Malay tafasir, such as Tafsir al-Azhar and Tafsir al-Misbah. Employing qualitative, descriptive and library research, this article analyses the influence of al-Ghazali on Malay tafasir and contributes to a deeper understanding of the development of the aspect of revelation and reason in the Malay-Muslim context and its resonance with al-Ghazali’s thought.